2015
DOI: 10.1007/s10616-014-9818-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia on proliferation of human cord blood-derived mesenchymal stem cells

Abstract: The purpose of our study was to examine the influence of hypoxia on proliferation of human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs). The mononuclear cells were separated by density gradient centrifugation from human umbilical cord blood and then, respectively, cultured under hypoxia (5 % O2) or normoxia (20 % O2). Their cell morphology, cell surface markers, β-galactosidase staining, cell growth curve, DNA cycle, and the expression of hypoxia-inducible factor-1α (HIF-1α) were evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…This result is discrepant to studies from Holzwarth et al [] demonstrating that hypoxic MSCs show increased Hif‐1α expression, which was associated with a decreased proliferation rate and accumulation of cells in G1 phase. However, other reports have demonstrated increased proliferation of MSCs in response to hypoxia [Grayson et al, ; Peng et al, ]. These controversial results may be explained by donor‐specific differences or by the origin of the tissues (adipose tissue, bone marrow, cord blood), from which the MSCs have been isolated, because it is known from the literature that MSCs isolated from different tissues may differ in their proliferation capacity and in their differentiation plasticity.…”
Section: Discussionsupporting
confidence: 56%
“…This result is discrepant to studies from Holzwarth et al [] demonstrating that hypoxic MSCs show increased Hif‐1α expression, which was associated with a decreased proliferation rate and accumulation of cells in G1 phase. However, other reports have demonstrated increased proliferation of MSCs in response to hypoxia [Grayson et al, ; Peng et al, ]. These controversial results may be explained by donor‐specific differences or by the origin of the tissues (adipose tissue, bone marrow, cord blood), from which the MSCs have been isolated, because it is known from the literature that MSCs isolated from different tissues may differ in their proliferation capacity and in their differentiation plasticity.…”
Section: Discussionsupporting
confidence: 56%
“…Similar to previous works, the results of our experiments showed that oxygen levels do not influence the morphology [ 31 , 48 , 53 , 67 ] or phenotype of MSCs [ 27 , 34 , 35 , 42 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 57 , 60 , 61 , 65 ], and these features did not differ between cells cultured under 21% O 2 and 5% O 2 . The hWJ-MSCs exhibited similar morphology and expressed surface antigens at similar levels under both investigated oxygen levels.…”
Section: Discussionsupporting
confidence: 91%
“…The role of different oxygen conditions in mesenchymal stem cell biology has been studied by other researchers, who investigated the influence of low oxygen tension (1–5%) on mesenchymal stem cells derived from bone marrow [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], adipose tissue [ 28 , 35 , 36 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], dental pulp [ 50 , 51 , 52 ], cord blood [ 53 , 54 ], the umbilical cord [ 45 , 55 , 56 ], and Wharton’s jelly [ 3 , 34 , 40 , 57 , 58 ]. However, studies on the effect of low oxygen levels on human WJ-MSCs were not comprehensive and have focused on a few cell properties.…”
Section: Introductionmentioning
confidence: 99%
“…As such, a 70‐kg person would require 70 × 10 6 cells for this purpose. These hurdles can probably be rectified with hypoxia culturing , application of bioreactors , usage of mitogenic factors such as human platelet lysate and basic fibroblast growth factors or combination of scaffolds , and perhaps by having proper storage/maintenance system adhering to cGMP (current Good Manufacture Practices) to ensure the delivery of a ‘cell drug’ that is not only safe but also reproducible as well as efficient . With the advancement of technology, the culturing can possibly be performed with automated devices which will reduce batch‐to‐batch variation when cells are scheduled to undergo upscaling for clinical applications.…”
Section: Discussionmentioning
confidence: 99%